Evaluating the Effectiveness of Midwife-Led Counseling on Maternal Knowledge, Attitudes, and Practices Related to Post-Immunization Adverse Events - Faridah; Nila Desta Sari; Rizka Novariani; Sri Wahyuni Yundasari; Risnawati (Jurnal Penelitian Pendidikan IPA, 2025)
Immunization is a key strategy to enhance individual immunity through the body's memory response. Adequate maternal knowledge regarding post-immunization adverse events (AEFI) is essential to promote awareness and ensure the completion of the recommended immunization schedule. Counseling is one of the most effective approaches to improve mothers’ understanding and attitudes toward AEFI. This study aimed to determine the effectiveness of midwife-led counseling in improving mothers’ knowledge and attitudes regarding AEFI. A quantitative pre-experimental design using a one-group pretest–posttest approach was employed. The study involved 45 mothers with children aged 0–9 months. Data on knowledge were analyzed using the Mann–Whitney test, while attitudes were assessed using the Wilcoxon signed-rank test. A significant improvement was observed in maternal knowledge following the counseling intervention (p = 0.000). Similarly, maternal attitudes showed a significant increase after counseling (p = 0.000). These findings indicate that midwife-led counseling effectively enhances both knowledge and attitudes related to AEFI. Counseling provided by midwives is effective in improving maternal knowledge and attitudes regarding post-immunization adverse events. Broader community engagement is recommended to support the dissemination of information on the early management of AEFI